Merger and Its Impact on Strengthening the Development of Sharia Banks in Indonesia - Rosmiati, Ii; Ropei, Ahmad; Ramadhani, Febri; Suharto, Suharto (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Sharia banking in Indonesia today continues to experience development in line with the increasingly advanced growth of the shari'ah economy. This is of course caused by many factors, including the existence of regulations that support the development of Islamic banking, especially related to the merger of Islamic banking. This shari'ah bank merger needs to be seen as an important part of the development of shari'ah banking in Indonesia. This paper is a type of qualitative research with the method used is the study of literature. The results of this paper reveal that the background of the merger of Islamic banks was the desire to strengthen the condition of Islamic banking in Indonesia by increasing the financial literacy of the Indonesian Muslim community. The merger of Islamic banks has had an impact on the development of Islamic banks in Indonesia, including after the merger, Bank Syariah Indonesia was able to become the 7th best national level bank; able to generate greater assets; increasing the total amount of financing, third party funds, and profits and succeeding in increasing shari'ah financial literacy in Indonesia.